Preparation method and application of zirconium alloy surface coating
By using magnetron sputtering technology to deposit the M5Si3-SiC biphasic co-grid structure coating on the surface of zirconium alloy, the problem of micro-wear and oxidation of zirconium alloy in high temperature and high pressure environments is solved, significantly improving its hardness and stability and extending its service life.
Patent Information
- Application Number
- CN202510078276.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-18
AI Technical Summary
Zirconium alloys are prone to micro-wear and oxidation in high-temperature and high-pressure environments, especially under complex high-temperature vibration conditions, the Zr total surface coating is prone to fall off and wear is intensified, threatening the service life and safety of zirconium alloy components.
Magneto-controlled sputtering technology is used to deposit a duplex coating on the surface of zirconium alloy, and the M5Si3-SiC biphasic co-grid structure coating is formed by cosputtering of multi-component refractory alloy targets, graphite targets and Si targets.
It significantly improves the hardness and plastic toughness of the surface coating of zirconium alloy, enhances its stability and fatigue resistance in high-temperature micro-wear environments, and extends the service life of zirconium alloy components.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal surface engineering, and in particular relates to a technical method for strengthening the surface of a zirconium alloy. Background Art
[0002] Zirconium and zirconium alloys are widely used in the fields of nuclear industry, aerospace, chemical equipment, etc. due to their excellent properties such as good corrosion resistance, high temperature stability and low neutron absorption cross section. In particular, they have great application potential as cladding materials in nuclear reactors. However, zirconium alloys are prone to severe micro-motion wear and oxidation in high temperature and high pressure environments. Especially under complex high temperature and vibration conditions, the surface coating of Zr alloys is prone to fall off and wear is aggravated, threatening the service life and safety of zirconium alloy parts. Therefore, improving the wear resistance of zirconium alloys in micro-motion wear environments, especially in the application of nuclear industry, has become an urgent problem to be solved.
[0003] Existing studies have shown that the presence of reinforcing phase carbides and silicides will hinder the expansion of cracks and increase the hardness of the coating. By preparing TiC, SiC, and other carbide and silicide reinforced composite coatings on the surface of zirconium alloys, their wear resistance and oxidation resistance can be improved to a certain extent, and their performance in high-temperature and complex environments can be improved. However, these composite coatings still have some shortcomings: First, the size of the reinforcing phase added to these coatings is too large (micrometer level), which is easy to form stress concentration under high-temperature micro-wear conditions, and the coating is prone to peeling and cracking; second, there is the problem of thermal matching of the reinforcing phase in the coating. The thermal expansion coefficient between the coating and the substrate is quite different, resulting in weak interface bonding, affecting the long-term stability of the coating; third, the performance of these coatings shows limited applicability under extreme working conditions, and it is difficult to meet the new high-demand application scenarios of zirconium alloys.
[0004] In recent years, high entropy silicide coatings developed based on the design concept of high entropy alloys have shown better performance than traditional coating materials due to their multi-principal element effects and lattice distortion characteristics. High entropy silicide not only inherits the high hardness, high temperature resistance and wear resistance of traditional silicide coatings, but also shows better oxidation resistance and corrosion resistance. Due to the synergistic effect of multiple principal element elements, high entropy silicide coatings have excellent stability and fatigue resistance in high-temperature micro-motion wear environments, and the lattice distortion effect effectively reduces the thermal conductivity of the coating, further improving the high-temperature heat resistance of the coating. These superior properties make high entropy silicide coatings an ideal choice for solving the micro-motion wear problem of zirconium alloys, especially suitable for applications in the nuclear industry and other harsh working conditions.
[0005] However, there are still some technical challenges in the application of existing high entropy silicide coating technology on zirconium alloy surfaces. For example, single-phase high entropy silicide often has a mismatch between strength and toughness, and the coating is prone to cracking. By forming a high entropy silicide and SiC dual-phase coherent structure in situ in the coating, the hardness and plastic toughness of the coating can be significantly improved. This provides an effective design idea for improving the performance and service life of Zr alloy cladding. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a method for preparing a zirconium alloy surface coating. The coating has excellent high hardness, high temperature resistance and wear resistance, and provides a solution to the fretting wear problem of zirconium alloys in the nuclear industry. A method for preparing a zirconium alloy surface coating, the steps are as follows: (1) Grinding and polishing the surface of the zirconium alloy substrate, and then ultrasonically cleaning the polished zirconium alloy substrate. After cleaning, drying with nitrogen gas, and fixing the zirconium alloy substrate on the sample table; (2) Installing the zirconium alloy substrate sample disk in the chamber of a multi-target magnetron sputtering instrument, closing the chamber door and sequentially evacuating the chamber to a high vacuum, heating the substrate, introducing an inert gas, adjusting the deposition pressure, opening the substrate baffle, turning on the power supply and performing coating deposition, using a multi-component refractory alloy target, a graphite target and a Si target as target materials, and a zirconium alloy as a substrate, adopting magnetron sputtering technology to co-sputter deposit to obtain a two-phase coating, taking out the coating sample after the temperature is cooled and storing it in a vacuum environment to obtain a zirconium alloy surface coating, wherein the multi-component refractory alloy target is at least five elements of Cr, Ta, Nb, Ti, V, Mo, W and Zr.
[0007] The surface cleaning of the substrate in step (1) is as follows: the zirconium alloy substrate is single-sidedly polished with 600-2000# sandpaper, and the polished zirconium alloy substrate is ultrasonically cleaned with deionized water and anhydrous ethanol in turn for 15-20 minutes.
[0008] The conditions for coating deposition in step (2) are as follows: the distance between the multi-component refractory alloy target, the graphite target and the Si target and the substrate is 6 mm, the back vacuum is 5.4×10 -4 - 8.6×10 -4 Pa, heating temperature is 300-800℃, deposition time is 18-30h, bias power supply power is 60-200V, sputtering power of multi-component refractory alloy target is controlled to 400mA, sputtering power of graphite target is 100~420mA, sputtering power of Si target is 160-300W, argon flow rate is 20sccm, gas purity of argon is ≥99.999%, after sputtering, cool to 60~80℃.
[0009] In the step (2), the deposition power sources for the multi-component refractory alloy target and the graphite target are high-power pulsed DC power sources, and the deposition power source for the Si target is a radio frequency power source.
[0010] The technical method for strengthening the surface of a zirconium alloy is applied to the fuel cladding zirconium alloy in a nuclear reactor.
[0011] The beneficial effects of the present invention are as follows: the surface of the zirconium alloy surface coating obtained by the present invention is dense and smooth, and exhibits a M5Si3 SiC two-phase coherent structure, with a thickness of 10.2-15.6 μm, a hardness of 14.8-35.6 GPa, and a wear rate of 1.7×10 4 -5.2×10 4 μm 2 The high-power pulsed DC power supply, radio frequency power supply and bias power supply adopted in the present invention can produce a dense coating structure with uniform element distribution. By using a multi-component refractory alloy target, Si target and graphite target separately, the atomic ratio of metal elements, Si and C elements can be effectively controlled.
[0012] The zirconium alloy surface coating contains a duplex coherent structure. Under the nuclear reactor operating environment, a dense oxide film is formed on the coating surface to prevent the oxidation of the Zr alloy. The duplex coherent structure in the coating gives the coating excellent wear resistance and hardness, which can effectively improve the service life of the Zr alloy in micro-wear and extend its service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0014] Figure 1 The SEM images of the coatings prepared in Examples 1-4 of the present invention; Figure 2 Scratch SEM images of the coatings prepared in Examples 1-4 of the present invention; Figure 3 XRD patterns of the coatings prepared in Examples 1-4 of the present invention; Figure 4 The hardness of the coating prepared in Examples 1-4 of the present invention; Figure 5 The curve of the change of oxidation weight gain over time of the coating prepared in Example 3 of the present invention and the Zr substrate under the working environment; Figure 6 The graph of the bonding strength variation of the coatings prepared in Examples 1-4 of the present invention; Figure 7 The friction coefficient of the coating and the Zr substrate prepared in Example 3 of the present invention varies with time; Figure 8 This is the structure of M5Si3 and SiC in the coating prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0015] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0016] The following Examples 1 to 4 were prepared according to the above-mentioned zirconium alloy surface strengthening technology, wherein the process parameters were different. The microstructure and mechanical properties of the coatings prepared in the examples were characterized, including the coating morphology, scratch morphology, wear area and volume change diagram.
[0017] Example 1 A method for preparing a zirconium alloy surface coating, the steps are as follows: (1) Grinding and polishing the surface of the zirconium alloy substrate, and then ultrasonically cleaning the polished zirconium alloy substrate. Specifically, the zirconium alloy substrate is ground and polished with 600#, 1200#, and 2000# sandpaper in sequence. The ground and polished zirconium alloy substrate is ultrasonically cleaned with deionized water and anhydrous ethanol for 15 to 20 minutes in sequence. After cleaning, it is dried with nitrogen and fixed on the sample plate; (2) Install the zirconium alloy substrate sample disk in the chamber of a multi-target magnetron sputtering instrument, close the chamber door and sequentially evacuate the chamber to a high vacuum, heat the substrate, introduce inert gas, adjust the deposition pressure, open the substrate baffle, turn on the power supply and perform coating deposition, using a multi-component refractory alloy target, a graphite target and a Si target as target materials, and a zirconium alloy as a substrate, and adopting magnetron sputtering technology to co-sputter deposit to obtain a two-phase coating, and after the temperature is cooled, take out the coating sample and store it in a vacuum environment to obtain a zirconium alloy surface coating, wherein the multi-component refractory alloy target is composed of seven elements: Cr, Ta, Ti, V, Mo, W and Zr.
[0018] The coating deposition conditions are as follows: the distance between the multi-component refractory alloy target, the graphite target and the Si target and the substrate is 6 mm, the back vacuum is 7.6×10 -4Pa, the heating temperature is 300-800℃, the deposition time is 18-30h, the bias power supply power is 60-200V, the sputtering power of the multi-component refractory alloy target is controlled to be 400mA, the sputtering power of the graphite target is 100 ~ 420 mA, the sputtering power of the Si target is 160-300W, the argon flow rate is 20 sccm, the gas purity of the argon is ≥99.999%, and after sputtering, it is cooled to a temperature of 60 ~ 80℃.
[0019] The deposition power sources of the multi-component refractory alloy target and the graphite target are high-power pulsed DC power sources, and the deposition power source of the Si target is a radio frequency power source.
[0020] The specific process parameters for preparing the in-situ dual-phase coating on the surface using magnetron sputtering technology in this embodiment are: the back vacuum is 6.8*10 -4 Pa, the distance from the target to the substrate surface is 5 mm, the deposition temperature is set to 370°C, the deposition bias power supply power is -60 V, the flow rate of the inert gas argon is set to 20 sccm, the deposition pressure of the coating is 0.5 Pa, the sputtering power of the multi-component refractory alloy target is 400 ma, the sputtering power of the graphite target is 100 ma, the sputtering power of the Si target is 300 W, the coating deposition time is 32 h, and the sample is taken out after cooling to 60°C.
[0021] The test results of this embodiment show that: Cr 15.4%, V 5.4%, Ti 4.3%, Nb 5.7%, Ta 6.3%, Mo 5.3%, W 4.9%, Zr 5.4%, Si 39.5%, C 7.8%; the phase structure of the coating is as follows: Figure 3 As shown in the middle line a, it shows a M5Si3, SiC two-phase coherent structure; the coating thickness is 11.2 µm; the hardness of the coating is 23.4 GPa, and the wear rate is 3.2×10 4 µm 2 .
[0022] Example 2 A method for preparing a zirconium alloy surface coating is disclosed, referring to Example 1, except that the multi-component refractory alloy target comprises seven elements: Cr, Ti, Nb, Ta, Mo, W, and Zr.
[0023] The specific process parameters for preparing the in-situ dual-phase coating on the surface using magnetron sputtering technology in this embodiment are: the back vacuum is 5.4*10 -4Pa, the distance from the target to the substrate surface is 6 mm, the deposition temperature is set to 450°C, the deposition bias power supply power is -60 V, the flow rate of the inert gas argon is set to 20 sccm, the deposition pressure of the coating is 0.5 Pa, the sputtering power of the multi-component refractory alloy target is 400 ma, the sputtering power of the graphite target is 180 ma, the sputtering power of the Si target is 240 W, the coating deposition time is 27 h, and the sample is taken out after cooling to 60°C.
[0024] The test results of this embodiment show that: Cr 18.3%, Ti 6.5%, Nb 5.7%, Ta5.6%, Mo 5.4%, W4.7%, Zr 5.2%, Si34.3%, C 14.3%; the phase structure of the coating is as follows: Figure 3 As shown in the middle line b, it shows a M5Si3-SiC two-phase coherent structure; the coating thickness is 13.6 µm; the hardness of the coating is 28.6 GPa, and the wear rate is 1.6×10 4 µm 2 .
[0025] Example 3 A method for preparing a zirconium alloy surface coating is disclosed, referring to Example 1, except that the multi-component refractory alloy target comprises five elements: Cr, Ta, Nb, Ti, and Zr.
[0026] The specific process parameters for preparing the in-situ dual-phase coating on the surface using magnetron sputtering technology in this embodiment are: the back vacuum is 8.6*10 -4 Pa, the distance from the target to the substrate surface is 5 mm, the deposition temperature is set to 500°C, the deposition bias power supply power is -60 V, the flow rate of the inert gas argon is set to 20 sccm, the deposition pressure of the coating is 0.5 Pa, the sputtering power of the multi-component refractory alloy target is 400 ma, the sputtering power of the graphite target is 340 ma, the sputtering power of the Si target is 180 W, the coating deposition time is 29 h, and the sample is taken out after cooling to 60°C.
[0027] The test results of this embodiment show that: Cr 27.4%, Ti 4.9%, Nb 4.8%, Ta 5.8%, Zr 5.7%, Si 29.6%, C 24.3%, and the phase structure of the coating is as follows: Figure 3 The middle line c and Figure 8 As shown in the figure, it shows a M5Si3-SiC two-phase coherent structure; the thickness of the coating is 14.0 µm; the hardness of the coating is 37.3 GPa, and the wear rate is 2.6×10 4 µm 2 .
[0028] Example 4 A method for preparing a zirconium alloy surface coating is disclosed, referring to Example 1, except that the multi-component refractory alloy target comprises six elements: Cr, Ta, Nb, Ti, W, and Zr.
[0029] The specific process parameters for preparing the in-situ dual-phase coating on the surface using magnetron sputtering technology in this embodiment are: the back vacuum is 7.9*10 -4 Pa, the distance from the target to the substrate surface is 5 mm, the deposition temperature is set to 650°C, the deposition bias power supply power is -60 V, the flow rate of the inert gas argon is set to 20 sccm, the deposition pressure of the coating is 0.5 Pa, the sputtering power of the multi-component refractory alloy target is 400 ma, the sputtering power of the graphite target is 420 ma, the sputtering power of the Si target is 160 W, the coating deposition time is 28 h, and the sample is taken out after cooling to 60°C.
[0030] The test results of this embodiment show that: Cr 19.1%, Ti 5.8%, Nb 4.5%, Ta4.9%, W 5.7%, Zr4.8%, Si 21.5%, C33.5%, the phase structure of the coating is as follows: Figure 3 As shown in the middle line d, it shows M5Si3, MC, SiC structure; the thickness of the coating is 15.2 µm; the hardness of the coating is 16.4 GPa, and the wear rate is 4.2×10 4 µm 2 .
[0031] In the above embodiments, the purity of the multi-component refractory alloy target is greater than 99.999%, the purity of the graphite target is greater than 99.99%, and the purity of the Si target is greater than 99.9%.
[0032] The contents of Cr, Ta, Nb, Ti, V, Mo, W, Zr, Si and C in the above-mentioned coating are 15.4%-27.4%, 5.1%-6.3%, 5.2%-5.7%, 5.3%-5.7%, 5.1%-5.4%, 5.8%-6.7%, 5.5%-6.2%, 5.6%-6.5%, 30%-40% and 5%-20%, respectively.
[0033] The coatings prepared in Examples 1-4 were tested, and the results were as follows: The coating samples were prepared by FIB to prepare TEM cross-section samples, and the structure of the coating samples was analyzed by transmission electron microscopy (TEM, FEI TecnaiG2 F20). The microscopic morphology of the coating was characterized by field emission scanning electron microscopy (SEM, Sigma 300). EDS point scanning was used to analyze the element distribution of the coating. X-ray diffractometer (XRD, XRO-6100) was used to analyze the composition changes of the coating under different compositions.
[0034] Figure 1 The surface morphology of the dual-phase coating prepared in Examples 1-4 of the present invention is smooth and flat.
[0035] Figure 2 The scratched surface morphology of the dual-phase coating prepared in Examples 1-4 of the present invention, the coating is basically not detached, and has excellent bonding strength.
[0036] Figure 3 The XRD patterns of the dual-phase coatings prepared in Examples 1-4 of the present invention show a typical M5Si3 and SiC dual-phase coherent structure in the coatings.
[0037] Figure 4 The hardness of the dual-phase coating prepared in Examples 1-4 of the present invention is significantly improved, which is beneficial to improving the service life of the coating.
[0038] Figure 5 The curve of the oxidation weight gain of the dual-phase coating prepared in Example 3 of the present invention and the Zr substrate under working conditions over time is as follows. Under working conditions, a dense oxide film is formed on the surface of the coating on the surface of the Zr alloy, which greatly reduces the weight gain caused by oxidation of the Zr alloy.
[0039] Figure 6 The bonding strength variation graph of the dual-phase coating prepared in Examples 1-4 of the present invention shows that the bonding strength of the coating is significantly improved, which can effectively prevent the coating from falling off under working conditions.
[0040] Figure 7 This is a curve showing the change in friction coefficient between the dual-phase coating and the Zr substrate prepared in Example 3 of the present invention over time. The coating prepared on the surface of the Zr alloy is beneficial to reducing its friction coefficient and increasing the service life of the Zr alloy.
[0041] Figure 8 The dual-phase coherent structure of M5Si3 and SiC in the dual-phase coating prepared in Example 3 of the present invention is shown in the figure. It can be seen from the figure that SiC is evenly dispersed in the coating. The coating presents M5Si3 and SiC dual phases.
[0042] The zirconium alloy surface coating of the above embodiment is used in the fuel cladding zirconium alloy of a nuclear reactor.
[0043] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. A method for preparing a zirconium alloy surface coating, characterized in that: Here are the steps: (1) Grinding and polishing the surface of the zirconium alloy substrate, and then ultrasonically cleaning the polished zirconium alloy substrate. After cleaning, drying with nitrogen gas, and fixing the zirconium alloy substrate on a sample plate; (2) Installing the zirconium alloy substrate sample disk in the chamber of a multi-target magnetron sputtering instrument, closing the chamber door and sequentially evacuating the chamber to a high vacuum, heating the substrate, introducing an inert gas, adjusting the deposition pressure, opening the substrate baffle, turning on the power supply and performing coating deposition, using a multi-component refractory alloy target, a graphite target and a Si target as target materials, and a zirconium alloy as a substrate, adopting magnetron sputtering technology to co-sputter deposit to obtain a two-phase coating, taking out the coating sample after the temperature is cooled and storing it in a vacuum environment to obtain a zirconium alloy surface coating, wherein the multi-component refractory alloy target is at least five elements of Cr, Ta, Nb, Ti, V, Mo, W and Zr.
2. The method for strengthening the surface of zirconium alloy according to claim 1, characterized in that: The surface cleaning of the substrate in step (1) is as follows: the zirconium alloy substrate is single-sidedly polished with 600-2000# sandpaper, and the polished zirconium alloy substrate is ultrasonically cleaned with deionized water and anhydrous ethanol in turn for 15-20 minutes.
3. A technical method for strengthening the surface of a zirconium alloy according to claim 1 or 2, characterized in that: In the step (1), the zirconium alloy substrate is ground and polished using 600#, 1200# and 2000# sandpapers in sequence.
4. The method for surface strengthening of zirconium alloy according to claim 1, characterized in that: The conditions for coating deposition in step (2) are as follows: the distance between the multi-component refractory alloy target, the graphite target and the Si target and the substrate is 6 mm, the back vacuum is 5.4×10 -4 - 8.6×10 -4 Pa, heating temperature is 300-800℃, deposition time is 18-30h, bias power supply power is 60-200V, sputtering power of multi-component refractory alloy target is controlled to 400mA, sputtering power of graphite target is 100 ~ 420mA, sputtering power of Si target is 160-300W, argon flow rate is 20 sccm, gas purity of argon is ≥99.999%, after sputtering, cool to a temperature of 60 ~ 80℃.
5. A technical method for strengthening the surface of a zirconium alloy according to claim 1 or 4, characterized in that: In the step (2), the deposition power sources for the multi-component refractory alloy target and the graphite target are high-power pulsed DC power sources, and the deposition power source for the Si target is a radio frequency power source.
6. Use of the zirconium alloy surface coating prepared according to claim 1 in the fuel cladding zirconium alloy of a nuclear reactor.